The effects of prosthetic status and dementia on the chewing efficiency of seniors in nursing homes - Klotz, Anna-Luisa; Schwindling, Franz Sebastian; Hassel, Alexander J.; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of oral rehabilitation, 2020)
Background - The oral health of seniors in nursing homes is compromised. Furthermore, reduced chewing efficiency is described to be associated with reduced cognition. However, studies investigating how prosthetic status affects the chewing efficiency of nursing home residents are not available.